Fine Root Size and Morphology of Associated Hyphae Reflect the Phosphorus Nutrition Strategies of European Beech Forests - Loew, Caroline A. E.; Schack-Kirchner, Helmer; Fink, Siegfried; Lang, Friederike (Frontiers in Forests and Global Change, 2020)
Roots are among the major controls of nutrient and C cycles and together with mycorrhizal fungi they are assumed to play a key role especially in P nutrition of forest ecosystems. Current publications emphasized that size distribution of fine roots reflects the crucial impact of roots on biogeochemical cycles. However, we know hardly anything about the spatial distribution of fine root size classes and their specific surface as well as distribution of mycorrhizal fungi among different size classes in undisturbed soils. We used a novel method based on epifluorescence microscopy to analyze fine roots in undisturbed soil samples. We expected that based on these analyses proposed differences between P-rich and P-poor soils get clearer than based on routine methods for fine root analysis. This was examined at two European beech forests in Germany at silicate rock that differ in P supply by the parent material. We analyzed the fine root frequency, size distribution and surface based on resin impregnated cross sections taken from undisturbed soil samples. Fine roots were classified according to their size and morphology of associated ectomycorrhiza with epifluorescence microscopy. More than 82% of the absorbing surface was associated with roots having a diameter smaller than 100µm. The fine root surface area present per square meter of soil was 388m² at the P-poor site and 220m² at the P-rich site. In addition, percentage of mycorrhization of fine root surface was 47% at P-poor site and only 38% at P-rich site. The biggest root length density and the highest absorbing fine root surface with mycorrhization and abundance of extramatrical mycelia was observed in forest floor at the P-poor site and in subsoil at P-rich site. Our results confirm that beech trees adapt their root traits according to P availability showing higher absorbing surface at the P-poor site compared to the P-rich site. In contrast, at the soil-profile scale, rooting density and mycorrhization increased with P availability thereby showing an efficient way of root and mycorrhizal fungi placement. Overall, distinct differences in fine root traits, between the P-rich and P-poor site were most evident for fine roots smaller than 100μm.